當代生命倫理學危機的根源及解決方案——David Solomon文章評析: Origins of and Responses to the Contemporary Crisis in Bioethics - Review of David Solomon’s Artivle - LEI, Ruipeng (International Journal of Chinese & Comparative Philosophy of Medicine, 2014)
LANGUAGE NOTE | Document text in Chinese; abstract in English only. David Solomon proposes in his article that deep divisions in our culture, which are reflected in the variety and opposition of foundational normative theories, are key to understanding the contemporary crisis in bioethics. Solomon examines two recent attempts to respond to this crisis of authority in bioethics and suggest that both proposals make the situation worse. However, his criticism of principlism, which has been dominant in bioethics since the 1980s, seems implausible. As observed by Aristotle, the rationale of a principle-based approach lies in the tensions between generality, considered judgment and ethical deliberation. The principle-based approach to meta-ethics is characterized as a dialectic between moral principles and considered judgment, which is analogous to Rawls’s concept of reflective equilibrium. The four principles formulated by Beauchamp and Childress are prima-facie binding, but subject to specification and balancing. It is possible for us to overcome these deep foundational disagreements in normative ethics by emphasizing the foundational principle held by the ancient Greeks; that is, our natural desire to live a good life. DOWNLOAD HISTORY | This article has been downloaded 41 times in Digital Commons before migrating into this platform.